Characterization of cellulose from oil palm empty fruit bunches by fast delignification process with different solvents - Firda Dimawarnita; Yora Faramitha; Haryo Tejo Prakoso; Indah Puspitasari; Doni Nugroho Kalbuadi; Dedy Prasetyo (Menara Perkebunan, 2023)
Cellulose extraction typically begins with a delignification reaction using conventional methods, namely alkaline treatment. So far, the delignification process using alkaline treatment requires quite a long time, which is over 6 hours of the cooking process, so the cost to produce cellulose is quite large. The delignification approach using a variety of solvents is needed to answer the current problem, which is to shorten the reaction time. In this study, two types of solvents were carried out for the delignification process of EFB, namely NaOH and H2O2, while the time used for the delignification process was 15 minutes. Parameters of research observations included levels of lignin, cellulose, and hemicellulose.Extraction of cellulose from EFB using H2O2 and NaOH produced cellulose content of 52.76% and 66.46%, respectively. However, based on visual results of treatment using NaOH are still brown in color which indicates that lignin is still contained in EFB. The Fourier Transform Infra Red (FTIR)and X-Ray Diffraction (XRD) characterization results before and after delignified EFB showed that a peak of 3301.75 cm−1 dominated the functional group that show cellulose, with the highest crystallinity index of 12.43% in the H2O2 treatment. The results of Thermogravimetry Analysis (TGA)and Scanning Electron Microscopy (SEM) analyses showed that EFB before and after treatment were different, which can be observed from the loss of lignin structure and TGA values which began to degrade at 351.78°C. Therefore, based on this research the best solvent for fast delignification of EFB was H2O2 (only need 15 min).